TRANSFORMING RURAL SECONDARY SCHOOLS IN ZIMBABWE THROUGH TECHNOLOGY: LIVED EXPERIENCES OF STUDENT COMPUTER USERS - Gomba Clifford (Informascope, 2016)
A technological divide exists in Zimbabwe between urban and rural schools that puts rural based students at a disadvantage. In Zimbabwe, the government, through the president donated computers to most rural schools in a bid to bridge the digital divide between rural and urban schools. The purpose of this phenomenological study was to understand the experiences of Advanced Level students using computers at two rural boarding Catholic High Schools in Zimbabwe. The study was guided by two research questions: (1) How do Advanced level students in the rural areas use computers at their school? and (2) What is the experience of using computers for Advanced Level students in the rural areas of Zimbabwe? By performing this study, it was possible to understand from the students' experiences whether computer usage was for educational learning or not. The results of the phenomenological study showed that students' experiences can be broadly classified into five themes, namely worthwhile (interesting) experience, accessibility issues, teachers' monopoly, research and social use, and Internet availability. The participants proposed teachers use computers, but not monopolize computer usage. The solution to the computer shortage may be solved by having donors and government help in the acquisitioning of more computers.